Faktor-faktor yang mempengaruhi Kualitas Laporan Keuangan: Sistem Informasi Akuntansi, Sistem Pengendalian Intern dan Kompetensi Sumber Daya Manusia - Dina Juniarti Barokah; Cris Kuntadi; Rachmat Pramukty (Universitas Katolik Widya Karya Malang, 2023)
This article reviews the factors that influence the quality of financial statements, namely accounting information systems, internal control systems and human resource competencies, a literature study on accounting information systems. The purpose of this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Accounting Information Systems affect the Quality of Financial Statements; 2) The Internal Control System affects the Quality of Financial Statements; and 3) Competence of Human Resources influences the Quality of Financial Statements.